2017
DOI: 10.3201/eid2307.170226
|View full text |Cite
|
Sign up to set email alerts
|

Contaminated Stream Water as Source for Escherichia coli O157 Illness in Children

Abstract: In May 2016, an outbreak of Shiga toxin–producing Escherichia coli O157 infections occurred among children who had played in a stream flowing through a park. Analysis of E. coli isolates from the patients, stream water, and deer and coyote scat showed that feces from deer were the most likely source of contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…It was reported in 2017 that Shiga toxin-producing Escherichia coli O157 caused infection in children who had played in a stream flowing through a park. According to them, their results revealed that faeces from deer were most likely the source of contamination of the stream [32]. Faeces of animals and humans could harbour Shiga toxin-producing Escherichia coli O157 that is why intensive monitoring, especially of faecal pollution arising from building toilets on water bodies, the use of faeces as manure and defecating in water bodies is important in understanding the extent of this pollution problem.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported in 2017 that Shiga toxin-producing Escherichia coli O157 caused infection in children who had played in a stream flowing through a park. According to them, their results revealed that faeces from deer were most likely the source of contamination of the stream [32]. Faeces of animals and humans could harbour Shiga toxin-producing Escherichia coli O157 that is why intensive monitoring, especially of faecal pollution arising from building toilets on water bodies, the use of faeces as manure and defecating in water bodies is important in understanding the extent of this pollution problem.…”
Section: Discussionmentioning
confidence: 99%
“…Shiga toxin-producing Escherichia coli (STEC) has been associated with numerous foodborne outbreaks around the world and causes severe illnesses, such as hemorrhagic colitis, bloody diarrhea, and hemolytic-uremic syndrome (Nüesch-Inderbinen et al, 2018). STEC can be easily disseminated and can cause human illness through direct contact with animal feces, contaminated irrigation water, and fecal-oral contamination of food items (Guy et al, 2014;Colello et al, 2016;Kennedy et al, 2017;Probert et al, 2017;Browne et al, 2018). E. coli O157:H7 was the first STEC strain discovered and was associated with contaminated burger patties in 1982; it has recently been related to leafy green outbreaks in multiple states (Juska et al, 2000;CDC, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There is an indeterminate risk associated with non-point source pollution events, such as fecal deposition from some wildlife. Moreover, the lack of a clear connection or correlation with these input sources reflects the inherent difficulty in characterising non-point source inputs, but there is some evidence that these sources may also contribute pathogens (Probert et al, 2017).…”
Section: Introductionmentioning
confidence: 99%